1996
DOI: 10.1093/infdis/174.1.75
|View full text |Cite
|
Sign up to set email alerts
|

The Repertoire of Human Antibodies to the Carbohydrate Capsule of Streptococcus pneumoniae 6B

Abstract: Antibodies to Streptococcus pneumoniae 6B capsular polysaccharide (PS) induced with a 23-valent PS vaccine among 25 adults were examined. The magnitude of antibody responses among different subjects was highly correlated with the amount of anti-6B antibodies expressing IgG (r = 0.98) and lambda (r = 0.93) isotypes. Most individuals produced one or two dominant IgG antibody clones as identified by their isoelectric points. Two antibody clones with unique amino acid sequences could be readily purified, and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
6
21
0
Order By: Relevance
“…First, only one or two distinct Fab fragments of any single serotype specificity were isolated from an individual donor, and in some cases these appeared to be intraclonal variants. This result is consistent with previous studies showing that Ab responses to PPS Ags are markedly oligoclonal and can be dominated by the products of a single clone (31,34,46). Second, the MNC populations used for library construction were enriched for specific B cells using PPS-coated paramagnetic beads and were obtained 7 days after vaccination, a time when there is an increased frequency of PPS-specific B cells in the peripheral circulation (38).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, only one or two distinct Fab fragments of any single serotype specificity were isolated from an individual donor, and in some cases these appeared to be intraclonal variants. This result is consistent with previous studies showing that Ab responses to PPS Ags are markedly oligoclonal and can be dominated by the products of a single clone (31,34,46). Second, the MNC populations used for library construction were enriched for specific B cells using PPS-coated paramagnetic beads and were obtained 7 days after vaccination, a time when there is an increased frequency of PPS-specific B cells in the peripheral circulation (38).…”
Section: Discussionsupporting
confidence: 89%
“…Although this interest stems primarily from the need to evaluate vaccine immunogenicity and to establish reliable surrogates of protection, the Ab response to PPS antigens (Ags) represents an ideal opportunity to examine the inheritance and development of protective immunity in humans. Ab responses to PPS Ags are markedly oligoclonal within individuals (31,34,46), and consequently variable (V) region diversity is limited. This property leads to individual variation in PPS-specific Ab fine specificity (41), avidity, and protective efficacy (52,66).…”
mentioning
confidence: 99%
“…Overall, the isolated heavy chain genes were 87.3 to 100% identical to germ line sequences, with the majority of the mutations occurring in the CDRs. Previous studies demonstrated a similar range of mutations in response to polysaccharide antigens (3,20,27,37,39,49,50).…”
Section: Discussionmentioning
confidence: 63%
“…Whereas the latter had been shown only for protein antigens, this report is the first to demonstrate that the XenoMouse repertoire is sufficient to generate an antipolysaccharide response. More work is needed to establish how closely the anti-PPS response of XenoMouse mice resembles that of humans, since the repertoire of XenoMouse mice does not contain a human locus and the light chain contributes to the human antibody response to PPS (27,32). However, our finding that like antibodies to PPS from humans (3,25,27,40), XenoMouse-derived MAbs to PPS 3 use V H 3 genes suggests that the anti-PPS response in these animals is restricted to V H 3 as it is in humans.…”
Section: Discussionmentioning
confidence: 99%